Performance of green funds - Sarkar, Patrick (2021)
Global warming is becoming an issue and there is a wide consensus that everyone should care for environment. Investment in financial asset markets can also contribute to the actions to reduce global warming. However, if the investments are not profitable enough then it is difficult for investors to invest in environmental causes. This study assesses the performance of USA domicile based Green Equity Funds from five different categories: Healthcare Sector, Mid Cap Category, Large Cap Growth Category, Large Cap Value Category, and Technology Sector. The funds were selected based on Morningstar’s ESG ratings as well as performance ratings and designation for low carbon emission. Since only the high-performance based funds are selected from Morningstar’s rating, for comparison purpose high performance-based funds from USAnews.com ranking are selected. Monthly return data are used to conduct the study over a period of 129 months from December 2010 to August 2021. Different factor models: CAPM, Fama French Three Factor Model, Carhart’s Four Factor Model, Fama French Five Factor Model and very recently introduced q5 Factor Model have been used to analyse the performance of the funds. Besides that, some descriptive statistics like average excess return, standard deviation, kurtosis, and skewness are also analysed in the study. The results show that considering only average excess return the conventional funds performed better than the green funds. However, the results from the factor models show that the return of the conventional funds and green funds are not statistically different. All the funds are sensitive to the market risk factor, some funds are sensitive to the value risk factor from Fama French and Carhart’s factor models and only few founds are sensitive to investment and profitability risk factors. Overall, the study shows that there is no difference in the financial returns of conventional and green funds. Investors who are investing in the green funds if not gaining superior return compared to the conventional funds, at least are not losing anything.